Concurrent validity of a new screening test to evaluate the information processing speed - Camila Fernanda Cabrera Zavala; Oscar Agustín Porta; Alén Martín; Edison Vega Valderrama; María del Rosario Lis; Wilson Gualotuña Pachacama; Diana Soto (Dementia & Neuropsychologia)
ABSTRACT Information processing speed (IPS) evaluates the time at which a person reacts to a stimulus. The Wechsler for Adults-III (WAIS-III) includes this domain in the digit symbol test (DS-T). Objective: The aim of this study was to validate a new screening test that could measure the IPS in association with the individual’s age and scholarship. Methods: A new instrument to measure the IPS was constructed, automatic cashier test (AC-T), and for its validation, the DS-T was also carried out. Results: The media of time use in the ACT was 12.3 s; the media of hits in the DS-T was 38.8, with a p<0.0001 and R2: 0.40. Conclusion: P-value showed a linear association between the two tests, but the R2 results showed a low association between these. In the same way, the correlation between both tests is promising, since it shows that both are tests that measure the IPS in a different way with different constructs such as the verbal fluency test that is also used to evaluate IPS. On the other hand, both tests exposed that the scholarship positively influences the IPS.